Hegel and Bataille on Sacrifice. Issue 2 (25th June 2018) - Goggin, W. Ezekiel
Abstract: In Georges Bataille's view, the Hegelian interpretation of kenotic sacrifice as passage from Spirit to the Speculative Idea effaces the necessarily representational character of sacrifice and the irreducible non-presence of death. But Hegel identifies these aspects of death in the fragments of the 1800 System. In sacrificial acts, subjectivity represents its disappearance via the sacrificed other, and hence is negated and conserved. Sacrifice thus provides the representational model of sublation pursued in the Phenomenology as a propaedeutic to Science. Bataille's critique clarifies the fragments of the 1800 System, contextualizing Hegel's rehabilitation of kenotic sacrifice in the Phenomenology . Bataille's poetics parodies Hegelian kenosis via repetition of material difference, enacting an ecstatic temporality which Hegel perhaps suppresses as the condition of his system. Finally—if Bataille is correct in his assessment—the system would be subjected to a reversal, with radical implications for the philosophy of religion.